A companion to David Lewis - Loewer, Barry; Schaffer, Jonathan (Chichester, West Sussex ; Wiley Blackwell, 2015)
"Brings together outstanding Lewis scholars and leading philosophers to explain, discuss, and critically extend Lewis's seminal and wide-ranging work in original ways"--
Machine generated contents note: Notes on Contributors ix Part I Biography and New Work 1 1 Intellectual Biography of David Lewis (1941-2001): Early Influences 3 Stephanie R. Lewis 2 Counterparts of States of Affairs 15 David Lewis 3 Reply to Dana Scott, "Is There Life on Possible Worlds?" 18 David Lewis Part II Methodology and Context 23 4 Lewis's Philosophical Method 25 Daniel Nolan 5 On Metaphysical Analysis 40 David Braddon-Mitchell and Kristie Miller 6 A Lewisian History of Philosophy 60 Robert Pasnau 7 David Lewis's Place in Analytic Philosophy 80 Scott Soames Part III Metaphysics and Science 99 8 Humean Supervenience 101 Brian Weatherson 9 No Work for a Theory of Universals 116 M. Eddon and C.J.G. Meacham 10 Hume's Dictum and Metaphysical Modality: Lewis's Combinatorialism 138 Jessica Wilson 11 Truthmaking: With and Without Counterpart Theory 159 Phillip Bricker 12 How to Be Humean 188 Jenann Ismael 13 Where (in Logical Space) Is God? 206 Stephanie R. Lewis 14 De Re Modality, Essentialism, and Lewis's Humeanism 220 Helen Beebee and Fraser MacBride 15 David Lewis on Persistence 237 Katherine Hawley 16 "Perfectly Understood, Unproblematic, and Certain": Lewis on Mereology 250 Karen Bennett 17 Humean Reductionism about Laws of Nature 262 Ned Hall 18 Why Lewisians Should Love Deterministic Chance 278 Rachael Briggs 19 Lewis on Causation 295 Christopher Hitchcock Part IV Language and Logic 313 20 David Lewis on Convention 315 Ernie Lepore and Matthew Stone 21 Asking What a Meaning Does: David Lewis's Contributions to Semantics 328 Barbara H. Partee 22 Accommodation in a Language Game 345 Craige Roberts 23 Lewis on Reference and Eligibility 367 J.R.G. Williams 24 On the Nature of Certain Philosophical Entities: Set Theoretic Constructionalism in the Metaphysics of David Lewis 382 Gideon Rosen 25 Primitive Self-Ascription: Lewis on the De Se 399 Richard Holton 26 Counterfactuals and Humean Reduction 411 Robert Stalnaker 27 On the Plurality of Lewis's Triviality Results 425 Alan Hajek 28 Decision Theory after Lewis 446 John Collins 29 Lewis on Mereology and Set Theory 459 John P. Burgess Part V Epistemology and Mind 471 30 Lewis on Knowledge Ascriptions 473 Jonathan Schaffer 31 Humility and Coexistence in Kant and Lewis: Two Modal Themes, with Variations 491 Rae Langton 32 Analytic Functionalism 504 Wolfgang Schwarz 33 Lewis on Materialism and Experience 519 Daniel Stoljar Part VI Ethics and Politics 533 34 Lewis on Value and Valuing 535 Peter Railton 35 David Lewis's Social and Political Philosophy 549 Simon Keller Bibliography of the Work of David Lewis 562 Index 572 .
Includes bibliographical references and index.
Keywords: Lewis, David K. -- 1941-2001.; PHILOSOPHY / General